Benefits and barriers in a clinical research competency development scheme for low- and middle-income countries. Issue 1 (31st December 2022) - Casamitjana, Núria; Vahedi, Mahnaz; Davoren, Sarah; Kavoura, Eleni; Tallada, Joan; Yamaka, Sara; Launois, Pascal
ABSTRACT: Background: The EDCTP-TDR Clinical Research and Development Fellowship (CRDF) scheme has offered one-year clinical research training placements for early- and mid-career researchers from LMIC since 1999. Objective: Using the results of a 2018 external evaluation of the CRDF, the current article aims to identify the principal benefits for the main stakeholders of the CRDF scheme as well as the main barriers to accessing these benefits. Method: Data analysis was derived from an external evaluation of the CRDF scheme. Based on a logical framework approach, data for the external evaluation was collected through document review, interviews, focus groups, and questionnaires collected from the main stakeholder groups. The evaluation was structured along six main themes: relevance, effectiveness, efficiency, impact, sustainability, and equity. Results: The current paper focuses on the expected benefits, unexpected benefits, and barriers to enjoying benefits of the scheme for key stakeholders. Discussion: Expected benefits were aligned with the development of clinical research competencies, which is the objective of the scheme. Unexpected benefits centred on transferable professional skills in scientific leadership and knowledge translation. Barriers mainly were found around engagement with home institutions and the return and reintegration of fellows following the training period. Conclusions and Recommendations: Recommendations include further engagement with and support for home institutions and developing a formal framework for the development of transferable professional competencies, including leadership and knowledge transfer competencies.